Selected aspects of biophilosophical controversies in complex plant behaviour research - Kupczak, Rafał (Studia Philosophiae Christianae, 2018)
We are currently witnessing changes in the scientific perception of the world of plants. Fundamental questions raised by scientists relate to the organization of plant life and concern the way in which signals are received from both the internal and external environment, and their acceptance or rejection depending on the potential consequences for the whole plant. The traditional understanding of plants as organisms devoid of sensual nature has undergone changes in favour of the conviction that advanced processes indicating intelligent plant behaviour could actually exist. The emergence of this new paradigm of research has triggered numerous disputes and controversies, both among scientists and philosophers.